2009
DOI: 10.1017/s0022215109990430
|View full text |Cite
|
Sign up to set email alerts
|

Use of botulinum toxin in voice restoration after laryngectomy

Abstract: Botulinum toxin can be used as a safe and cost-effective treatment in patients with confirmed pharyngoesophageal segment hypertonicity and/or spasm following laryngectomy, to obtain an improvement in voice quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
(61 reference statements)
0
2
0
1
Order By: Relevance
“…In confirming objective efficacy, these findings are in accordance with those reported previously. 8,9 However, comparison between studies is impeded by the considerable variation in outcome measurements. 14,15 The largest study to dateby Hamaker and Blom 16 used intra-tracheal phonation pressures in a similar manner to our study to assess outcomes in 62 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In confirming objective efficacy, these findings are in accordance with those reported previously. 8,9 However, comparison between studies is impeded by the considerable variation in outcome measurements. 14,15 The largest study to dateby Hamaker and Blom 16 used intra-tracheal phonation pressures in a similar manner to our study to assess outcomes in 62 patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have evaluated objectively use of botulinum for PES spasm, and demonstrated its efficacy in the context of dysphonia and dysphagia. 8,9 However, there is ENT Ann R Coll Surg Engl 2015; 97: 508-512 doi 10.1308/rcsann.2015.0011 a paucity of data relating to patient-reported outcome measures and treatment of PES spasm-induced CVL. We sought to evaluate objective and patient-perceived outcomes with respect to dysphagia, dysphonia and CVL.…”
mentioning
confidence: 99%
“…Bu konuda yap›lan bir meta-analizde 1966-2009 y›llar› aras›nda Medline'da yay›nlanm›fl 9 klinik çal›flma ve 134 olgu incelenmifl; objektif ses kalitesi de¤erlendirildi¤inde baflar› oran›n›n %70-100 oldu¤u bildirilmifltir. Yazarlar larenjekomiden sonra faringoözefageal segmentte hipertonisite ve/veya spazm oldu¤u kan›tlanm›fl hastalarda BTX'un güvenli ve maliyet etkin bir flekilde kullan›labilece¤i sonucuna varm›fllard›r (45).…”
Section: Larenjektomize Ses Protezi Tak›lan Hastalarunclassified